ChemInform Abstract: Structure and Biological Activity of 8‐Deoxyheronamide C from a Marine‐Derived Streptomyces sp.: Heronamides Target Saturated Hydrocarbon Chains in Lipid Membranes. Issue 41 (7th October 2014) - Sugiyama, Ryosuke; Nishimura, Shinichi; Matsumori, Nobuaki; Tsunematsu, Yuta; Hattori, Akira; Kakeya, Hideaki
Abstract Title compound (I), a new 20‐membered polyene macrolactam, is a unique membrane binder.